Generalizations of some Enestrom-Kakeya type results - Gulzar, MH; Manzoor, AW (BIBECHANA, 2015)
In this paper we give interesting generalizations of some well-known Enestrom-Kakeya type results on the location of zeros of a complex polynomial under less restrictive conditions on the coefficients of the polynomial. BIBECHANA 13 (2016) 1-8